1998
DOI: 10.1098/rstb.1998.0319
|View full text |Cite
|
Sign up to set email alerts
|

Why are there so few resistance–associated mutations in insecticide target genes?

Abstract: The genes encoding the three major targets of conventional insecticides are: Rdl, which encodes a g-aminobutyric acid receptor subunit (RDL); para, which encodes a voltage-gated sodium channel (PARA); and Ace, which encodes insect acetylcholinesterase (AChE). Interestingly, despite the complexity of the encoded receptors or enzymes, very few amino acid residues are replaced in di¡erent resistant insects: one within RDL, two within PARA and three or more within AChE. Here we examine the possible reasons underly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0
4

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(65 citation statements)
references
References 60 publications
2
59
0
4
Order By: Relevance
“…Our results are generally comparable with observations of the effects of dieldrin and fipronil on resistant RDL subunit of Drosophila (Wolff and Wingate, 1998). When mutated, RDL-containing GABA receptor acquire resistance to picrotoxinin and dieldrin (Hosie et al, 1997;ffrench-Constant et al, 1998). Resistance to fipronil in these cases is variable compared with susceptible counterparts, whereas a low resistance ratio to fipronil was reported in sensitive and resistant strains of Blatella germanica (for review see Bloomquist, 2001).…”
Section: Discussionsupporting
confidence: 78%
“…Our results are generally comparable with observations of the effects of dieldrin and fipronil on resistant RDL subunit of Drosophila (Wolff and Wingate, 1998). When mutated, RDL-containing GABA receptor acquire resistance to picrotoxinin and dieldrin (Hosie et al, 1997;ffrench-Constant et al, 1998). Resistance to fipronil in these cases is variable compared with susceptible counterparts, whereas a low resistance ratio to fipronil was reported in sensitive and resistant strains of Blatella germanica (for review see Bloomquist, 2001).…”
Section: Discussionsupporting
confidence: 78%
“…Thus, the Ala 301 to Ser or Gly mutation in Rdl exhibits unique properties, providing high levels of dieldrin resistance without abolishing the role of the RDL receptor (12). Electrophysiological studies showed that the 301 replacement affects cyclodiene sensitivity by two mechanisms: inhibiting direct binding and allosterically modifying the Rdl receptor to disrupt the antagonist-favored conformation (13).…”
mentioning
confidence: 99%
“…Insecticide resistance has been reported from many insects including A. gambiae that showed the presence of insensitive acetylcholinesterase in two different populations that were resistant to carbosulfan, a carbamate insecticide (N'Guessan et al, 2003). Mutations at a single codon in the Rdl (resistance to dieldrin) gene have been documented in all dieldrinresistant insects, and confer both insensitivity to the insecticide and a decrease rate of desensitisation (ffrench-Constant et al, 1998). However, in A. gambiae this type of resistance mechanism has not been described so far.…”
Section: Target Site Resistancementioning
confidence: 99%